![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
4个回答
展开全部
解由(2x-1)^2(3x+2)-(2x-1)(3x+2)^2-x(1-2x)(3x+2)
=(2x-1)^2(3x+2)-(2x-1)(3x+2)^2+x(2x-1)(3x+2)
=(3x+2)(2x-1)[(2x-1)-(3x+2)+x]
=(3x+2)(2x-1)[2x-1-3x-2+x]
=(3x+2)(2x-1)[-3]
=-3(3x+2)(2x-1)
=(2x-1)^2(3x+2)-(2x-1)(3x+2)^2+x(2x-1)(3x+2)
=(3x+2)(2x-1)[(2x-1)-(3x+2)+x]
=(3x+2)(2x-1)[2x-1-3x-2+x]
=(3x+2)(2x-1)[-3]
=-3(3x+2)(2x-1)
展开全部
(2x-1)²(3x+2)-(2x-1)(3x+2)²-(1-2x)(3x+2)
=(2x-1)²(3x+2)-(2x-1)(3x+2)+(2x-1)(3x+2) 把1-2x变成2x-1
=(2x-1)(3x+2)(2x-1-3x-2+x) 提取公因式(2x-1)(3x+2)
=-3(2x-1)(3x+2)
=(2x-1)²(3x+2)-(2x-1)(3x+2)+(2x-1)(3x+2) 把1-2x变成2x-1
=(2x-1)(3x+2)(2x-1-3x-2+x) 提取公因式(2x-1)(3x+2)
=-3(2x-1)(3x+2)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
原式=(2x-1)²(3x+2)-(2x-1)(3x+2)²+x(2x-1)(3x+2)
=(2x-1)(3x+2)[(2x-1)-(3x+2)+x]
=-3(2x-1)(3x+2)
=(2x-1)(3x+2)[(2x-1)-(3x+2)+x]
=-3(2x-1)(3x+2)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
2013-04-23
展开全部
解原式=(2x-1)(3x+2)[(2x-1)-(3x+2)+x]=(2x-1)(3x+2)(-3)=3(1-2x)(3x+2)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询